50. NARRATIVE REVIEW ABOUT THE INTERVENTION ON EARLY INITIATION OF EARLY BREASTFEEDING INITIATION DURING 2015-2024 (Tạp chí Y học Cộng đồng, 2024)
Background: Although early initiation of breastfeeding could save the lives of thousands newborn, it is a far from mother’s practice worldwide. This narrative review paper aims to identify and describe intervention activities intended to increase the initiation of early breastfeeding during 2015-2024.Materials and Method: The search was undertaken from January to March, 2024. The methods and reporting were developed and conducted with the guideline of PRISMA reporting guidelines. Search terms were applied with various Boolean operators for three core concepts: breastfeeding; timing of breastfeeding initiation; and hospital-based interventionResult: 14 studies were included for review. After more than three decades of implementation (1991-present), reports on 168 countries in 2017 show that the majority of countries (86%) have implemented BFHI. WHO estimates that BFHI coverage (calculated as the proportion of children born at BFHIs) was only 10% in 2016. BFHI coverage varies by region, with coverage rates above 35% in Europe but less than 5% in Africa and Southeast Asia.Conclusion: Whilst some barriers manifest similarly across the region some factors are context-specific thus tailored interventions are imperative. Initiatives halting factors and directed towards contextual barriers are required for greater impact on newborn survival and improved nutrition in low- and middle-income countries.
Keywords: early initiation of breastfeeding; narrative review; hospital-based intervention